2018
DOI: 10.3390/molecules23061259
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Amino Acid Content in Onions as Potential Fingerprints of Geographical Origin: The Case of Rossa da Inverno sel. Rojo Duro

Abstract: In this study, we were interested in comparing the amino acid profile in a specific variety of onion, Rossa da inverno sel. Rojo Duro, produced in two different Italian sites: the Cannara (Umbria region) and Imola (Emilia Romagna region) sites. Onions were cultivated in a comparable manner, mostly in terms of the mineral fertilization, seeding, and harvesting stages, as well as good weed control. Furthermore, in both regions, the plants were irrigated by the water sprinkler method and subjected to similar temp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…The chromatogram of an extract is exemplarily shown in Figure 1. As expected [18,21], the selected IP-RP-HPLC-ELSD method, produced the co-elution of Ala/Glu and Ser/Asn (data not shown). Moreover, interfering matrix effects were found in the first 18 min of each sample analysis, thus impairing the detection of certain amino acids (data not shown).…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…The chromatogram of an extract is exemplarily shown in Figure 1. As expected [18,21], the selected IP-RP-HPLC-ELSD method, produced the co-elution of Ala/Glu and Ser/Asn (data not shown). Moreover, interfering matrix effects were found in the first 18 min of each sample analysis, thus impairing the detection of certain amino acids (data not shown).…”
Section: Resultssupporting
confidence: 73%
“…A direct ion-pairing reversed-phase method based on the use of the evaporative light-scattering detector (IP-RP-HPLC/ELSD) was applied for the analysis of the milk extracts. The method was previously developed in our laboratory and profitably employed for the direct analysis of amino acids in complex food matrices [18,21]. Detailed information on the method is reported in the caption to Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A growing number of studies have demonstrated that geographical sources could significantly affect the quality of these herbs, since climate and environment influence biosynthesis and the accumulation of secondary metabolites in organisms [8,9,10]. Cortex Periplocae is widespread in Shanxi, Henan, Hebei, and Shandong provinces in China [11,12], and there are no standard planting grounds for it [13].…”
Section: Introductionmentioning
confidence: 99%